2003
DOI: 10.12921/cmst.2003.09.01.67-78
|View full text |Cite
|
Sign up to set email alerts
|

Two Interacting Particles in a Parabolic Well: Harmonium and Related Systems*

Abstract: The quasi-exactly solvable problem of two interacting electrons confined by a parabolic potential (harmonium) has been generalized for the case of two arbitrary particles. Several new features of the analytical solutions are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Spectral properties are studied as a function of Debye screening length d . We have also verified our results with the those of Karwowski et al [37] (not shown here) that the comparison ensures the effectiveness of our method. In Table 1 energy eigenvalues of harmonium without Debye effect are shown.…”
Section: Resultssupporting
confidence: 90%
“…Spectral properties are studied as a function of Debye screening length d . We have also verified our results with the those of Karwowski et al [37] (not shown here) that the comparison ensures the effectiveness of our method. In Table 1 energy eigenvalues of harmonium without Debye effect are shown.…”
Section: Resultssupporting
confidence: 90%
“…The excited states can be obtained accurately. 99,100 One excited state is treated here, the first of the same symmetry as the ground state, E(µ = ∞) = 2.9401169 . .…”
Section: System: Harmoniummentioning
confidence: 99%
“…To explore whether the model potentials can be used to describe repulsive interactions, we consider a system of two interacting electrons confined in a harmonic oscillator potential, called Harmonium [21,22]. The Hamiltonian of Harmonium is: the center of mass and the relative coordinates…”
Section: Harmoniummentioning
confidence: 99%